Innovation Strategies for Reducing Greenhouse Gas Emissions Using the Design Thinking Method: A Case Study at the Offshore Field of XYZ Oil and Gas Company - Ageng Premana; Octaviyanti Dwi Wahyurini (Journal of Social Research, 2026)
This study aims to identify the main sources of GHG emissions, explore potential innovation opportunities, and formulate emission reduction strategies that align with the operational conditions of XYZ Oil and Gas Company's Offshore Field. This research employed the Design Thinking 3-IDEO model, which consists of Inspiration, Ideation, and Implementation stages. Data were collected through field observations, document analysis, in-depth interviews, stakeholder mapping, empathy maps, user personas, user journey maps, point of view (PoV), and how might we (HMW) analyses. The respondents included various stakeholders directly involved in offshore field operations. The collected data were analyzed qualitatively to identify user needs, operational challenges, and innovation opportunities that support emission reduction initiatives. The results indicate that the primary sources of GHG emissions originate from flare systems, fuel consumption in gas turbine compressors and generators, well unloading and well intervention activities caused by high back pressure, as well as diesel fuel consumption from offshore vessel operations. Through the ideation and stakeholder validation processes, four priority innovation strategies were identified: (1) utilization of gas released from the primary seal gas system as additional fuel gas, (2) optimization of operating pressure through modifications to existing facilities, (3) optimization of vessel operations through procedural improvements, and (4) installation of electrical submersible pumps (ESP) powered by micro turbine generators. All proposed strategies demonstrate strong alignment with ESG principles, operational excellence objectives, and the Sustainable Development Goals (SDGs), while offering potential environmental, operational, and economic benefits in a sustainable manner.